Sosialisasi dan Pendampingan Penulisan Karya Ilmiah bagi Kelompok Kerja Guru Gugus Dewantara Kabupaten Blora - Rahmanti Asmarani; Budi Santoso; Sri Oemiati; Pipiet Furisari (ASPIRASI : Publikasi Hasil Pengabdian dan Kegiatan Masyarakat, 2024)
Competence of writing scientific articles is a requirement for teachers to apply for promotion. Lack of time to write scientific papers and the inability to express ideas in writing are obstacles for teachers in writing scientific papers. For those reasons, the program delivered by Community service of Dian Nuswantoro universe encourages and motivates teachers of the Dewantara teachers’ working group in Blora district, to produce articles in scientific journals. This activity aims to increase the professional competence of teachers who are members of the Dewantara teachers’ working group in Blora district by training in writing scientific articles in Indonesian. Training is carried out through four stages, namely the preparation stage, implementation stage, monitoring and evaluation stage, and service results reporting stage. The results show that during the training the participants showed high enthusiasm in writing scientific articles. The limited training time means further participant discussions and consultations can be carried out online or via e-mail.